2013
DOI: 10.2298/abs1301161c
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate elements on the diameter increment of Austrian pine (Pinus nigra Arn.) in Serbia

Abstract: The aims of this paper were the analysis of climate elements and Thornthwaite’s climate index, the study of the development of diameter and current diameter increment of the Austrian pine trees from several artificial stands in the Belgrade area, as well as an analysis of the influences of the pluviometric regime and climate index on the current diameter increment of the Austrian pine over the period 1985-2010. By comparative analysis and statistical data procession, the correlation between the diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Unfavourable climate, especially the lack of precipitation during the growing season, air temperatures above multi-annual averages ( Tables S4–S7 ), and prolonged and frequent drought periods have had serious and long-term consequences on forest ecosystems in Serbia. Similar observations have been stated by domestic authors [ 53 , 54 , 55 , 65 , 66 , 67 , 68 , 69 , 70 ], whose research confirms the negative impacts of climate change and extreme climate events on the growth, development, and vitality of forest tree species and forest ecosystems as a whole.…”
Section: Discussionsupporting
confidence: 90%
“…Unfavourable climate, especially the lack of precipitation during the growing season, air temperatures above multi-annual averages ( Tables S4–S7 ), and prolonged and frequent drought periods have had serious and long-term consequences on forest ecosystems in Serbia. Similar observations have been stated by domestic authors [ 53 , 54 , 55 , 65 , 66 , 67 , 68 , 69 , 70 ], whose research confirms the negative impacts of climate change and extreme climate events on the growth, development, and vitality of forest tree species and forest ecosystems as a whole.…”
Section: Discussionsupporting
confidence: 90%
“…The fact that sufficient precipitation with a good distribution throughout the year has a strong positive influence on the radial growth of Austrian pine (Pinus nigra Arn.) was also observed in Serbia (Koprivica et al 2009, Ćirković-Mitrović et al 2013). According to Koprivica et al (2009), in middleaged Austrian pine plantations, a statistically significant dependence of the diameter increment on the precipitation was determined, whereas the dependence on the air temperature and thinning is random.…”
Section: Discussionmentioning
confidence: 61%
“…According to Koprivica et al (2009), in middleaged Austrian pine plantations, a statistically significant dependence of the diameter increment on the precipitation was determined, whereas the dependence on the air temperature and thinning is random. Ćirković-Mitrović et al (2013) found a strong positive correlation between the trends in the diameter increment of Austrian pine and annual precipitation, but also with precipitation during the growing season (Ćirković-Mitrović et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Poljanšek et al (2013) noted that "summer sunshine is tightly connected with moisture stress in trees, because the moisture stress and therefore the width of tree rings are under the influence of the direct and interactive effects of sunshine duration (temperature, precipitation, cloud cover and evapotranspiration)". Ćirković-Mitrović et al (2013) found a strong positive correlation between the tree ring-width of Austrian pine trees from three artificially established stands at three sites in the Belgrade area in Serbia and precipitation in the growing period.…”
Section: Discussionmentioning
confidence: 87%